Comparing sessile benthos on shallow artificial versus natural hard substrates in the Eastern Mediterranean Sea - SEDANO, FRANCISCO; FLORIDO, MARTA; RALLIS, IOANNIS; ESPINOSA, FREE; GEROVASILEIOU, VASILIS (Mediterranean Marine Science, 2019)
Artificial structures cover a considerable part of the Mediterranean coasts. In the Aegean Sea, most studies related to artificial structures have focused in vagile fauna on harbors and marinas but little attention has been given to the sessile biota on coastal defense structures. The aim of this work was to describe for the first time the shallow sublittoral sessile benthos on coastal defense structures in Crete (Eastern Mediterranean Sea) in order to identify potential differences in comparison to natural rocky substrates, adopting both a taxonomic and functional (i.e. macroalgal structural complexity) approach. Three shallow (1-3 m) localities were studied in the north coast and three in the south coast of the island (six localities in total). At each locality, two types of hard substrate were selected: an artificial coastal defense structure (rip-rap) and the nearest natural rocky substrates. The percent cover of sessile taxa was calculated using random points counts over photoquadrats (20 x 20 cm). The structure of the assemblage differed between artificial and natural habitats. Values of Shannon-Wiener’s diversity index and number of taxa were higher in natural substrates. In addition, cover of arborescent macroalgae was lower on artificial substrates. In conclusion, rip-raps do not function as surrogates of natural hard substrates in the study area since their shallow subtidal assemblages differ in terms of community structure, diversity and functionality. The deficient performance of such artificial structures could be attributed to the combined effects of abiotic factors and biotic processes, including substrate nature and roughness as well as differential grazing pressure.